From Isotopes to TK Interviews: Towards Interdisciplinary Research in Fort Resolution and the Slave River Delta, Northwest Territories - Wolfe, Brent B.; Armitage, Derek; Wesche, Sonia; Brock, Bronwyn E.; Sokal, Michael A.; Clogg-Wright, Kenneth P.; Mongeon, Cherie L.; Adam, Margaret E.; Hall, Roland I.; Edwards, Thomas W.D. (ARCTIC, 2009)
Evolving research in Fort Resolution and the Slave River Delta, Northwest Territories, aims to improve understanding of how the natural ecosystem functions and responds to various environmental stressors, as well as to enhance the stewardship of natural resources and the capacity of local residents to respond to change. We seek to integrate approaches that span the natural and social sciences and traditional knowledge understandings of change, employing a research design developed in response to the concerns of a northern community. In doing so, we have strived for a research process that is collaborative, interdisciplinary, policy-oriented, and reflective of northern priorities. These elements characterize the new northern research paradigm increasingly promoted by various federal funding agencies, northern partners, and communities. They represent a holistic perspective in the pursuit of solutions to address complex environmental and socioeconomic concerns about impacts of climate change and resource development on northern societies. However, efforts to fulfill the objectives of this research paradigm are associated with a host of on-the-ground challenges. These challenges include (but are not restricted to) developing effective community partnerships and collaboration and documenting change through interdisciplinary approaches. Here we provide an overview of the components that comprise our interdisciplinary research program and offer an accounting of our formative experiences in confronting these challenges. Des travaux de recherche en cours à Fort Resolution et dans le delta de la rivière des Esclaves, aux Territoires du Nord-Ouest, visent à mieux comprendre le fonctionnement de l’écosystème naturel, à réagir aux divers facteurs d’agression environnementaux ainsi qu’à rehausser la gérance des ressources naturelles et la capacité des habitants de la région à réagir au changement. Nous cherchons à intégrer des méthodes qui englobent les sciences naturelles et sociales et favorisent la compréhension du ...